1989
DOI: 10.1063/1.344067
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reactions of titanium thin films on BF+2 -implanted (001)Si

Abstract: Interfacial reactions of titanium thin films on BF+2 -implanted (001)Si have been studied by both cross-sectional and planview transmission electron microscopy as well as by sheet resistivity measurement. Amorphous Ti-Si interlayers were observed in Ti films on blank and implanted samples following 400 °C annealing. The presence of the doping impurities was found to promote the early growth of the C54-TiSi2 phase. 100% surface coverage of TiSi2 on silicon was found in implantation amorphous samples annealed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, several groups reported small F containing bubbles forming in BF 2 ϩ -implanted polySi after annealing, but they were visible only under high-resolution cross-sectional TEM ͑XTEM͒. 26,34,49 Furthermore, their density decreases while their size increases with annealing temperature. 12,49 Immediately after the deposition of Ti, the Ti/Si interface does not react.…”
Section: Proposed Mechanism For Void Formation Inmentioning
confidence: 98%
See 1 more Smart Citation
“…However, several groups reported small F containing bubbles forming in BF 2 ϩ -implanted polySi after annealing, but they were visible only under high-resolution cross-sectional TEM ͑XTEM͒. 26,34,49 Furthermore, their density decreases while their size increases with annealing temperature. 12,49 Immediately after the deposition of Ti, the Ti/Si interface does not react.…”
Section: Proposed Mechanism For Void Formation Inmentioning
confidence: 98%
“…26,34,49 Furthermore, their density decreases while their size increases with annealing temperature. 12,49 Immediately after the deposition of Ti, the Ti/Si interface does not react. 3 Butz, Rubloff, and Ho and Hsu et al reported that Ti thin films on Si can be transformed to Ti 5 Si 3 , TiSi, and TiSi 2 after steady-state annealing between 500 and 600°C, and only TiSi 2 can be observed after annealing above 650°C.…”
Section: Proposed Mechanism For Void Formation Inmentioning
confidence: 98%
“…The growth of the amorphous phase at Ti-Si interfaces during low-temperature annealing (below 450°C) is now well-documented (e.g. 17,21,22 ) and results in non-ohmic contacts to p+ silicon in 0.3 micron via holes23. Holloway et al 24 have carefully considered the thermodynamic and kinetic conditions for the amorphous phase reaction, showing that it is energetically favored over the physical Ti-Si interface and can be produced so long as crystallization is avoided by fast diffusion of one species (i.e.…”
Section: Ti-si Interfacesmentioning
confidence: 99%
“…N 1 implantation was introduced in an attempt to suppress both channeling and TED. 9 In addition, the morphological stability of C54-TiSi 2 during high temperature annealing is crucial to the development of ULSI technology. Low-resistivity TiSi 2 is perhaps the most attractive candidate for the self-aligned technology of ULSI circuits because it possesses the lowest resistivity among all silicides, low contact resistance, and good thermal properties as well as compatibility with the self-aligned silicidation process.…”
Section: Introductionmentioning
confidence: 99%